Study Of Risk Factors of Perinatal Death in Pregnancy Induced Hypertension (PIH) - Parmar, Mehul T; Solanki, Harsha M; Gosalia, Vibha V (National Journal of Community Medicine, 2012)
Background: Hypertensive disorders are common complication occurring during pregnancy responsible for maternal & fetal mortality & morbidity. Though the condition is on decline, still stands a public health problem. Objectives: To determine risk factors of perinatal death in women with pregnancy induced hypertension. Materials & Method: A cross-sectional study was conducted over period of one year in the department of Obstetrics & Gynecology in NHL municipal college, Ahmadabad. A total of 100 pregnant women with PIH were enrolled in the study. A pre-tested structured Performa was prepared & women were interviewed to collect necessary information such as detailed history, clinical examination findings & investigations performed. Results were analyzed using MS Excel & Epi Info. Results: In the present study, 29%, 21% & 50 % were of mild PIH, moderate PIH & severe PIH respectively. The incidence of PIH was found more among teenage pregnancy, among primigravidas, those from low socio-economic status, those with history of PIH in previous pregnancy, having family history of PIH & those who were found obese. Emergency delivery, having diastolic blood pressure > 90 mm Hg, higher degree of proteinuria & low birth weight among PIH cases had an adverse perinatal outcome in terms of higher perinatal death. The findings were statistically significant On Univariate analysis; diastolic blood pressure & degree of proteinuria were found to be significant risk factors responsible for perinatal mortality among PIH women. Conclusion: Pregnancy induced hypertension is a common medical disorder associated with pregnancy. In the present study, PIH cases who delivered in emergency, with raised diastolic blood pressure & more proteinuria & neonate with low birth weight were found risk factors for perinatal death. Fetal morbidity & mortality can be reduced by early recognition & institutional management.